A3.2 A CD4+ T-Cell Gene Expression Signature Predicts Drug Survival on Methotrexate Monotherapy in Early Rheumatoid Arthritis. (25th February 2013) - Pratt, AG; Brown, PM; Cockell, SJ; Wilson, G; Isaacs, JD
Abstract : Background/Purpose: The mechanism of action of methotrexate (MTX) in the management of rheumatoid arthritis (RA) remains incompletely understood. Making use of an existing dataset, we investigated the CD4+ T-cell transcriptome in early RA patients, seeking biomarkers for drug survival on MTX monotherapy and associated pharmacological insights. Methods: In previous work [1] RNA was rapidly extracted from peripheral blood CD4+ T-cells of 173 early arthritis clinic attendees, at which time patients had been symptomatic for a median of 12 weeks, and were naïve to immunomodulatory treatments. Transcriptional profiling was undertaken using Illumina WG6v3 BeadChip oligonucleotide array technology. For this study a sub-cohort of RA patients was retrospectively identified, whose initial treatment with MTX monotherapy was continued for as long as deemed successful between patient and consulting rheumatologist. Intra-muscular steroid bolus administration (but not oral steroid therapy) was permitted during the study at the discretion of the consulting rheumatologist. MTX monotherapy survival after ≥1 year follow-up (median 28 months) was used as a surrogate outcome for efficacy, and bio informatics analysis was performed using GeneSpring XI (Agilent). Results: Amongst 31 eligible patients, 19 (61%) remained on MTX monotherapy at the end of follow-up, but the treatment strategy was unsuccessful (and required modification) for the remaining 12 (39%). Baseline characteristics and final methotrexate doses were comparable between the two groups. 133 CD4+ T-cell transcripts were identified as being differentially expressed between comparator groups at baseline (>1.2 fold-change; p < 0.05) and a metric derived from their normalised expression values demonstrated a promising discriminatory utility with respect to MTX mono- therapy survival (area under ROC curve 0.91). Functional analysis identified an over-representation of genes involved in apoptosis (11/133 genes; hypergeometric p = 0.000045). Conclusions: Although limited by its reliance on a surrogate efficacy outcome, our pilot study has identified potential transcriptional biomarkers for drug survival on MTX monotherapy amongst early RA patients. Alongside their potential clinical applicability, they suggest that this treatment's efficacy may depend on its ability to regulate CD4+ T-cell survival. Validation amongst a clinically well-characterised, independent early RA cohort is now on-going. Reference: Pratt AG et al, ARD 2012.